2000
DOI: 10.1159/000014618
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary Prolactin-Secreting Tumor Formation: Recent Developments

Abstract: Prolactinoma is the most common type of primary pituitary tumors. It occurs more frequently in women than in men. Dopaminergic agonists are effective in the shrinkage of prolactin-secreting pituitary tumor and are preferred in some patients. However, pituitary radiotherapy may enable the long-term removal of prolactin-secreting tumor cells. Recent evidence suggests that prolactinoma is a heterogeneous disorder with complicated and multifactorial etiology and pathogenesis. Apparently, a thorough understanding o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 74 publications
1
12
0
Order By: Relevance
“…In rats, fetal exposure to this drug results in an increase of prolactin in the lactotrope cells of the pituitary gland. In 20 women with advanced breast cancer, a phase 2 study in which patients were administered 400 mg/ day of cyproterone acetate produced an increment of prolactin levels (10). Moreover, in men with prostatic carcinoma, treatment with cyproterone acetate causes prolactin levels to rise.…”
Section: Discussionmentioning
confidence: 99%
“…In rats, fetal exposure to this drug results in an increase of prolactin in the lactotrope cells of the pituitary gland. In 20 women with advanced breast cancer, a phase 2 study in which patients were administered 400 mg/ day of cyproterone acetate produced an increment of prolactin levels (10). Moreover, in men with prostatic carcinoma, treatment with cyproterone acetate causes prolactin levels to rise.…”
Section: Discussionmentioning
confidence: 99%
“…The elevated glucocorticoid response may itself mediate the shortened lifespan by altering apoptosis rates (47)(48)(49); altering immune function (11) and, thus, susceptibility to tumor development (50); or inducing oxidative stress (47). Alternatively, the glucocorticoid profile may be associated with other physiological systems (e.g., sympathetic nervous system activation, amygdala, or dopaminergic activity) that may either enhance pituitary tumorgenesis (51) or, more generally, reduce the ability to handle a tumor load in neophobic individuals (e.g., increased heart rate, blood pressure, etc.). The animal model that we have developed provides an ideal system in which to conduct longitudinal and experimental studies to identify the neuroendocrine, molecular, and genetic mechanisms underlying early death in neophobic individuals.…”
Section: Discussionmentioning
confidence: 99%
“…In experimental animal studies it has been demonstrated, that prolonged administration of estradiol (E 2 ) induces prolactinomas [8][9][10]. On the other hand lactotrophs are known to proliferate during pregnancy and up to 30% of macroadenomas may grow during gestation [11].…”
Section: Introductionmentioning
confidence: 99%